Hubungan Kecerdasan Fluida dengan Kontrol Diri pada Mahasiswa Institut Teknologi Sumatera - Darmawan, Andy; Wulandari, Putri; Nurhayu, Winati (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Fluid intelligence is the ability to think quickl and flexibly in solving new problems without relying on past experiences. Meanwhile, self-control is the ability to carry out necessary tasks and resist unwanted and unnecessary temptations. Students, as individuals transitioning into adulthood, may have unique self-control and fluid intelligence due to ongoing brain development. This study aims to analyze the relationship between fluid intelligence and self-control among students at Sumatra Institute of Technology. The research method used in this study involved interviews using the Baddeley Reasoning Test and self-control Scale with 161 respondents, consisting of 73 males and 88 females. The results of the study indicate that there was no significant relationship between fluid intelligence and self-control. One factor that may explain higher fluid intelligence in males is that they are often required to make decisions. Additionally, higher self-control in females may be attributed to societal expectations of more normative behavior for women.